A short survey of network economics - Oz Shy (Federal Reserve Bank of Boston, 2010)
This paper surveys a variety of topics related to network economics. Topics covered include: consumer demand under network effects, compatibility decisions and standardization, technology advances in network industries, two-sided markets, information networks and intellectual property, and social influence.
Keywords: D4; L1; L8; Z1; 330; Survey; network economics; network industries; network effects; network externalities; Network Externalities; Netzwerk; Unternehmensnetzwerk; Theorie